Sense of Gloominess and Despair in Edgar Allan Poe’s Selected Poems: : An Analytical Approach - Hasan, Mariwan; Karim, Rayan; Muhsin, Sara (LPPM Universitas Advent Indonesia, 2024)
Edgar Allan Poe's life was plagued by melancholy and disaster, which is evident in all of his writings. Among the many other poets of his generation, his solitude and individuality set him apart from the rest. He gave the Gothic genre a completely new meaning, making it both dark and significant at the same time. First, as an overview is given, of the 19th century, Edgar Allan Poe, and the tragedies that influenced his poetry. This study employs a comprehensive methodology focusing on the close reading of three of Poe's well-known poems: